Cranial nerve palsies in patients with hematological malignancies: a case series. (2nd August 2020) - Diamanti, Luca; Berzero, Giulia; Franciotta, Diego; Bini, Paola; Furione, Milena; Farina, Lisa Maria; Bastianello, Stefano; Colombo, Anna Amelia; Marchioni, Enrico
Abstract: Objectives: Cranial neuropathies (CNs) can be due to a wide spectrum of causes, and the differential diagnosis is particularly challenging in patients with positive history of hematological malignancies, when neoplastic meningitis (NM) must be excluded. Patients and Methods: We retrospectively selected a series of twelve haematological patients with isolated cranial neuropathies (ICNs) or multiple cranial neuropathies (MCNs). among 71 patients that developed neurologic symptoms during different stages of the cancer, between 1 January, 2010 and 31 December, 2017. Brain and cauda equina magnetic resonance imaging (MRI) with gadolinium, cerebrospinal fluid (CSF) analysis, including flow cytometry for cell immunophenotyping and microbiological exams were performed in all patients. Results: Patients developed signs and symptoms of involvement of isolated ( n  = 11) or multiple ( n  = 1) cranial nerves, at different stages of the primary disease, and, in 5 of these cases in complete remission after hematopoietic stem cell transplantation. Among the 5 cases that eventually were diagnosed as having NM, cerebrospinal fluid was positive for neoplastic cells in 3, and MRI gadolinium-enhancement was present in 3. The other episodes were attributed to heterogeneous pathologies that were unrelated to meningeal infiltration by neoplastic cells. Conclusions: Our observations confirm that NM in haematological malignancies can yield insidious isolated signs of cranial nerves. Only a multidisciplinary approach allows prompt recognition of these conditions through a challenging process of differential diagnosis, and proper therapies.